2018
DOI: 10.1002/cyto.a.23348
|View full text |Cite
|
Sign up to set email alerts
|

Application of area scaling analysis to identify natural killer cell and monocyte involvement in the GranToxiLux antibody dependent cell‐mediated cytotoxicity assay

Abstract: Several different assay methodologies have been described for the evaluation of HIV or SIV‐specific antibody‐dependent cell‐mediated cytotoxicity (ADCC). Commonly used assays measure ADCC by evaluating effector cell functions, or by detecting elimination of target cells. Signaling through Fc receptors, cellular activation, cytotoxic granule exocytosis, or accumulation of cytolytic and immune signaling factors have been used to evaluate ADCC at the level of the effector cells. Alternatively, assays that measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 73 publications
1
32
0
Order By: Relevance
“…Using BAMA Fc arrays, we found higher levels of FcγR3a binding by immunocomplexes formed with rabbit IgG than RM IgG. Consistent with this observation, application of ASA to the results of the ADCC-GTL assay (73) demonstrated that rabbit serum preferentially recruited human NK cells. Moreover, we demonstrated that rabbit immune sera were able to induce a significantly higher frequency of NK cell CD107a degranulation (74) than RM sera.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Using BAMA Fc arrays, we found higher levels of FcγR3a binding by immunocomplexes formed with rabbit IgG than RM IgG. Consistent with this observation, application of ASA to the results of the ADCC-GTL assay (73) demonstrated that rabbit serum preferentially recruited human NK cells. Moreover, we demonstrated that rabbit immune sera were able to induce a significantly higher frequency of NK cell CD107a degranulation (74) than RM sera.…”
Section: Discussionsupporting
confidence: 75%
“…To test this, we applied area scaling analysis (ASA) to ADCC-GTL assays performed with gp120-coated target cells (described in the legend to Fig. 4) to discriminate the ability of antibodies to recruit NK cells and monocytes present in the PBMC used as a source of effector cells (73). Using ASA, we calculated the ratio of target cells that interacted with NK cells and monocytes in the presence of serum samples.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to ADCP, trogocytosis is another potential outcome of Fc-dependent interactions between antibodies and virus-infected cells. Two assays developed to measure HIV/SIV-specific ADCC responses have been shown to also detect antibody-mediated interactions between monocytes and virus-infected or protein-coated cells (177, 178). Both assays use fluorescent dyes to label infected or protein-coated target cells.…”
Section: Approaches To Measure Virus Adcpmentioning
confidence: 99%
“…The association of FcγRIIa binding with HIV-1 risk also remained significant in the IgA interaction model (OR = 0.405 [IgA -], P = 0.001; OR = 0.682 [IgA + ], P = 0.002) with the interaction P value being 0.200. Env IgG3 breadth is a weight-systemic HIV-1 infection, including clearance of virions that may decrease the number of functionally infectious virions to infect new cells and phagocytosis or trogocytosis of infected cells (54,55) that may limit their capacity to produce and spread new virions. Although our analysis showed no impact from IgG3, timing of exposure may be important to any impact on VL due to the rapid decline of Env IgG3 following vaccination (47).…”
Section: Volume 129 Number 11 November 2019mentioning
confidence: 99%